Influence of crystalline polyimide hard block on the properties of poly(imide siloxane) copolymers. (15th January 2015) - Pei, Xueliang; Chen, Guofei; Liu, Jiangtao; Fang, Xingzhong
Abstract: Comparative study was carried out regarding the properties of poly(imide siloxane) copolymers (PISs) with crystalline polyimide hard block and PISs with amorphous polyimide hard block. The crystalline polyimide hard block was synthesized from 3, 3′, 4, 4′-biphenyltetracarboxylic dianhydride (BPDA) and 1, 3-bis(4-aminophenoxy)benzene (TPER), and the amorphous polyimide hard block was synthesized from 2, 2-bis(4-(3, 4-dicarboxyphenoxy)phenyl)propane dianhydride (BPADA) and meta-phenylenediamine ( m -PDA). The polysiloxane soft block based on bis(γ-aminopropyl)polydimethylsiloxane (APPS) had a molecular weight of 995 g/mol, and the APPS content in monomers varied from 32.6 to 53.0 wt%. The crystallization of PISs with crystalline polyimide hard block was investigated by differential scanning calorimetry (DSC), wide-angle X-ray diffraction (WXRD) and polarized optical microscope (POM). It was found that the crystalline polyimide hard block was more effective in retaining storage modulus and improving solvent resistance and elastic property of the PISs than the amorphous polyimide hard block. Graphical abstract: Highlights: Thermal stability of PIS was improved by using crystalline polyimide block. Crystalline polyimide block was effective in improving elastic property of PIS. Crystalline polyimide block could improve the solvent resistance of PIS. Polysiloxane did not change the crystal structure of crystalline polyimide block.